REHABILITATION OF POST-STROKE PATIENTS IN THE EARLY RECOVERY PERIOD: A META-ANALYSIS OF THE SCIENTIFIC LITERATURE - Havrylenko, A. V.; Yashchyshyn, Z. M.; Popovych, D. V. (Rehabilitation and Recreation, 2025)
Recently, Ukraine has been implementing projects aimed at physical therapy for post-stroke patients in different periods of rehabilitation. Despite some successes in this area, the problem of motor and functional disorders remains insufficiently researched. The aim is to analyse the sources of scientific literature on the main areas of rehabilitation of patients in the early recovery period of intracerebral stroke. Material. Meta-analysis of publications, electronic search in the databases Web of Science, Scopus, Cochrane Library, PubMed, CrossRef, AO Braine, Eurobraine, ResearchGate, eLIBRARY, MEDLINE from the bibliography of key articles. Results. We analysed articles with publication dates from 2015 to 2024. The results of the review showed that the National and World Stroke Associations point to the need for a unified stroke programme aimed at addressing issues related to reducing mortality, disability and improving medical care. The rehabilitation processes for post-stroke patients are based on the following: early start, sequence, duration, active participation of the patient in the rehabilitation process and involvement of their relatives. When vital functions are stabilised, rehabilitation measures should begin as early as possible. According to many authors, the most effective means of rehabilitation and physical therapy (RPT) programmes are locomotor training to develop spatial movement skills. They also emphasise the importance of early exercise. Physical therapy is one of the most studied techniques and involves the use of special physical exercises to restore motor functions. The use of interactive programmes allows to stimulate motor functions, while encouraging the patient to actively participate in the recovery process. The scientific literature emphasises the importance of cognitive rehabilitation. Studies show that combined methods, such as verbal and cognitive exercises using computer programmes or group therapy, can increase the effectiveness of recovery. Psychological rehabilitation is an important part of the whole process. Pharmacotherapy can be used in case of severe mental disorders. Social rehabilitation, where the patient's participation in support groups, social clubs and other forms of collective activity helps to improve his or her condition. Vocational rehabilitation and training in new professional skills or adaptation of the work environment to the patient's characteristics are important aspects of the rehabilitation process. The latest technologies that can speed up the rehabilitation process include robotic systems, virtual reality, telemedicine and mobile applications that allow patients to perform rehabilitation exercises independently or under the remote supervision of a specialist. Conclusions. The analysis of the scientific literature showed that the development of neurorehabilitation methods is an urgent problem and is far from being resolved, and physical therapy programmes should be aimed at improving the effectiveness of motor function recovery.